Diagnostic evaluation of urea nitrogen/creatinine ratio in dogs with gastrointestinal bleeding - Jenny Stiller (Wiley, 2021)
Abstract Background Urea nitrogen/creatinine ratio (UCR) is a marker for upper gastrointestinal bleeding (GIB) in people. Objectives To assess the usefulness of UCR to predict occult GIB and distinguish upper from lower GIB in dogs. Animals Eighty‐nine dogs with GIB and 65 clinically healthy dogs. Dogs were grouped according to 65 overt GIB and 24 occult GIB, and based on lesion localization (37 upper, 13 lower, and 8 both). Methods Seventy‐four dogs were included retrospectively and 15 dogs prospectively. Serum urea nitrogen and creatinine concentrations, UCR, hemoglobin concentration, hematocrit, mean corpuscular volume, and mean corpuscular hemoglobin concentration were compared between groups. Logistic regression models were fitted to assess if variables could distinguish occult GIB from being healthy and upper from lower GIB. Results The UCR was significantly higher in dogs with overt GIB compared to control dogs (P = .02) and dogs with occult GIB (P = .05). The UCR was not significantly associated with occult GIB vs being healthy, or upper vs lower GIB (P > .05 each). Dogs with higher hemoglobin concentration and hematocrit had significantly lower odds of having occult GIB than being healthy (P < .0001 each). Conclusions and Clinical Importance The UCR does not seem to be a clinically useful marker of occult GIB and appears to have poor discriminatory ability between upper and lower GIB. An increased UCR in a dog without signs of overt GIB, especially if its hematocrit is within the middle or upper reference interval, does not appear to warrant prompt prescription of gastrointestinal protectants.